Spatial variation and hydrogeochemical characterization of groundwater in Vallanadu region: insights from water quality index and statistical analysis - D. Manimaran; S. Richard Abishek; V. Stephen Pitchaimani; A. Antony Ravindran; M. Soniyamary; Shankar Karuppannan (Discover Sustainability)
Abstract The present study aims to evaluate the seasonal variations of geochemistry and groundwater quality in the Vallanadu region. Groundwater samples collected during the pre-monsoon and post-monsoon periods were analyzed using spatial analysis, the Water Quality Index (WQI), rock-water interaction, Principal Component Analysis (PCA), and Hierarchical Cluster Analysis (HCA). The WQI analysis revealed a significant deterioration in groundwater quality, with 60% of pre-monsoon samples classified as “Good,” 30% as “Fair,” and 10% as “Poor,” compared to 15% “Good,” 30% “Fair,” and 55% “Poor” or “Hazardous” post-monsoon, highlighting seasonal changes' influence. Hydrogeochemical facies analysis, through Piper diagrams, identified mixed Ca2+-Mg2+-Cl− water as the dominant type, indicating marine intrusion and carbonate dissolution as major influencing factors. Rock-water interaction analysis highlighted silicate and carbonate weathering as primary geochemical processes, with seasonal recharge and evaporation shaping ion distributions. Statistical analyses including HCA and PCA, revealed distinct geochemical zones, with pre-monsoon periods showing higher ionic concentrations due to evaporation and reduced recharge, while post-monsoon periods were influenced by dilution and increased recharge. The findings underscore significant seasonal variations in groundwater quality and emphasize the growing impact of agricultural runoff, saline intrusion, and anthropogenic activities. The study highlights the urgent need for groundwater quality management in the Vallanadu region to ensure sustainable drinking and irrigation use.